Efektivitas Kinerja Pegawai dalam Meningkatkan Pelayanan pada Kantor Urusan Agama (KUA) Kecamatan Medan Johor - M. Ali Azmi Nasusion; Hasnah Hasnah; Rois Hamid Siregar (ISLAMIKA, 2023)
The Office of Religious Affairs (KUA) acts as a government agency assigned to an area to provide services to the community. However, the results obtained in the field showed that many people complained about the services provided by employees at the KUA. The purpose of this research is to reduce obstacles in carrying out the duties and functions that should be carried out by the Office of Religious Affairs in Medan Johor District. The method used in this study uses a qualitative approach which will then be explained in descriptive form. Data collection is carried out using primary data derived from direct observation, interviews and documentation of the local community and employees. The results found in this study are that there are still many obstacles that occur in carrying out effectiveness at the KUA Medan Johor District due to several factors, namely the lack of information and socialization provided to the community, employees who are less disciplined with time, and inadequate facilities.